Albatross - Kiesselbach, Dore (Pitt poetry series., 2017)
Dore Kiesselbach's second collection Albatross views the events of September 11th as a physicist might examine high-energy particles in a supercollider. In the book's central section, Kiesselbach, who worked three blocks from the World Trade Center and was an eyewitness, deconstructs the cultural hyperbole of that extraordinary day in a series of intimate portraits that dovetail elsewhere with a wider examination of violence in the everyday lives of individuals, families, and nations. While neither blaming victims, nor succumbing to despair, the book urges reflection on the roles we each play in our own harm. Like its namesake, the human-powered aircraft flown across the English Channel in 1979, Albatross invites readers to push forward into headwinds--public and private--and make for the far shore.s